Progress of physics understanding for long pulse high-performance plasmas on EAST towards the steady-state operation of ITER and CFETR. (5th December 2019) - Huang, J; Gong, X; Garofalo, A M; Qian, J; Chen, J; Wu, M; Li, M; Yuan, Q; Wang, L; Pan, C; Lin, X; Yang, Q; et al.
Abstract: Recently, the first ever 100 s long, steady-state H-mode discharge with good control of impurities, core and edge MHD stabilities, and heat exhaust was demonstrated in the Experimental Advanced Superconducting Tokamak (EAST) using the ITER-like (International Tokamak Experimental Reactor) tungsten upper divertor. Using both radio frequency (RF) power and neutral beam injection (NBI) heating, EAST has demonstrated fully non-inductive scenarios with an extension of fusion performance at high density and low rotation: β P ∼ 2.5, β N ∼ 2.0, H98, y2 ∼ 1.2, bootstrap current fraction fBS ∼50% at q95 ∼ 6.8. With pure RF power heating, plasmas have been maintained for up to 21 s (over 40 times the current relaxation time) with zero loop voltage and small edge localized modes (ELMs) at high density (ne /nGW ∼ 0.6–0.8), β P ∼ 2.0, β N ∼ 1.6, and ƒBS ∼47%. Experimental investigations show how plasma current profiles, turbulent transport and radiation properties self-consistently evolve toward fusion relevant steady state conditions. Modeling and physics experiments have confirmed the synergistic effects between electron cyclotron heating (ECH) and low hybrid wave (LHW), where ECH enhances the heating and current drive from LHW injection, enabling fully non-inductive operation at higher density. Small/no ELMs facilitate the RF power coupling in the H-mode phase and reduce divertor erosion. A low tungsten concentration was observed at high β P with a hollow profile in the core. Reduction of the peak divertor heat flux with f rad of up to 40% was compatible with the high β P scenario by using active radiation feedback control. With features such as dominant electron heating, zero/low NBI torque and an ITER-like tungsten divertor, fully non-inductive high-performance experiments on EAST offer unique contributions towards the succesful operation of ITER and CFETR (the Chinese Fusion Engineering Testing Reactor).